2018
DOI: 10.21276/ijcmr.2018.5.6.28
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Compliance with Full Immunization of Children Against Vaccine Preventable Diseases among Pregnant Mothers in Sokoto, Nigeria

Abstract: Introduction: Despite the fact that immunization is proven to be the most successful and cost-effective public health intervention in reducing childhood morbidity and mortality, full immunization coverage remains abysmally low in Nigeria, with a concomitant high burden of vaccine preventable diseases (VPDs) among children. This study aimed to assess the knowledge, attitude and compliance with full immunization of children against VPDs among pregnant mothers in Sokoto, Nigeria. Material and Methods: A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
4
4
1
Order By: Relevance
“…In this study, 336 (80.4%) of mothers have heard information about infant immunization and 241 (57.7%) of them have access to information from health workers followed by 189 (45.2%) radio and 103 (24.6%) television. This is similar to a study carried out in Addis Ababa, 23 Nigeria, 24 Saudi Arabia, 25 , 26 Pakistan, 27 India, 28–31 Nepal, 32 Afghanistan, 33 Lithuania, 34 and Georgia, 35 and health care workers were the major source of information. This might be due to nowadays most of the parents got delivery service at a health facility with skilled birth attendants and health care worker plays an indispensable role, during ANC and PNC period by convincing parents to link the newborn baby to Immunization unit to acquire immunization service as well as the intimate relationship between a service provider and the parents at primary health care levels and these health facilities seem to be most readily available and accessible to the people.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, 336 (80.4%) of mothers have heard information about infant immunization and 241 (57.7%) of them have access to information from health workers followed by 189 (45.2%) radio and 103 (24.6%) television. This is similar to a study carried out in Addis Ababa, 23 Nigeria, 24 Saudi Arabia, 25 , 26 Pakistan, 27 India, 28–31 Nepal, 32 Afghanistan, 33 Lithuania, 34 and Georgia, 35 and health care workers were the major source of information. This might be due to nowadays most of the parents got delivery service at a health facility with skilled birth attendants and health care worker plays an indispensable role, during ANC and PNC period by convincing parents to link the newborn baby to Immunization unit to acquire immunization service as well as the intimate relationship between a service provider and the parents at primary health care levels and these health facilities seem to be most readily available and accessible to the people.…”
Section: Discussionsupporting
confidence: 87%
“…Maternal knowledge on vaccine and VPDs was also revealed to in uence childhood immunization uptake in Southeast Ethiopia where children whose mothers had good knowledge on vaccine and VPDs were found to be three times as likely to be fully vaccinated compared with children that belongs to mothers who had poor knowledge on vaccine and VPDs [16]. Similar nding was also found in Nigeria [61]. Maternal knowledge on child vaccine schedule was revealedto be statistically in uencing child immunization uptake where mothers who had knowledge on schedules of vaccine were found to be four times as likely to fully immunize their children compared with mother who has no knowledge on vaccine schedule [29,53,59].…”
Section: Maternal Knowledgesupporting
confidence: 63%
“…Likewise, awareness on immunization and immunization program was also revealed in three studies [20,32,56]. Two studies reported the impact of knowledge of VPDs [16,61]. For maternal attitude and self-e cacy, three studies reported availability of child immunization record [20,24,43].…”
Section: Modi Able Factorsmentioning
confidence: 88%
“…Maternal knowledge on vaccines and VPDs were also shown to in uence childhood immunisation uptake in Southeast Ethiopia, where children whose mothers had a good knowledge on vaccines and VPDs were found to be three times more likely to be fully vaccinated compared with children of mothers who had a poor knowledge of vaccines and VPDs [16]. A similar nding was also found in Nigeria [61]. Maternal knowledge on child vaccine schedules was revealed to statistically in uence child immunisation uptake where mothers who had knowledge on schedules of vaccines were found to be four times more likely to fully immunise their children compared with mothers who has no knowledge of vaccine schedules [29,53,59].…”
Section: Maternal Knowledgesupporting
confidence: 58%